HUBUNGAN KARAKTERISTIK PEKERJA, KELENGKAPAN DAN HIGIENITAS APD DENGAN KEJADIAN DERMATITIS KONTAK (Studi Kasus Di Rumah Kompos Jambangan Surabaya) - Shenna Fielrantika Anggraitya Dhera (Universitas Airlangga, 2017)
Contact dermatitis is an inflammation of skin which is caused by a substance that sticks to somebody’s skin. The cause of contact dermatitis is physical factor, a substance of plants, and other chemicals. One of prevention contact dermatitis because of working is the usage of personal protection equipments like mask, gloves, goggles, shoes, and body protection. The objectives of this research was to analyze the relation between the characteristics of worker, the completeness and the hygiene of personal protection equipments with the contact dermatitis occurrence in the house of compost Jambangan Surabaya. The methodology of this research was observational using cross sectional approach. The target of this research was all workers who have worked in the house of compost Jambangan Surabaya as 21 people were taken by total sampling technique. The variable that was observed included contact dermatitis occurrence, gender, the history of skin allergy, age, knowledge, attitude, action, and the completeness of using personal protection equipments. The primer data was taken by interview with questionnaire paper and observation. The secondary data was taken from the house of compost Jambangan Surabaya. Then, data that was taken from questionnaire was analyzed by descriptive as the narration form. The result of this research explained that the completeness of using personal protection equipments by the worker have not completed yet and for the main characteristics of the worker was their knowledge. The conclusion was using complete personal protection equipments could prevent contact dermatitis of the worker in the house of compost Jambangan Surabaya. Keywords: Individual characteristics, Completeness and The hygiene of personal protection equipments, Contact dermatitis